Antiwrinkle efficacy of 1‐ethyl‐β‐N‐acetylglucosaminide, an inducer of epidermal hyaluronan production. Issue 1 (29th August 2021) - Endo, Yoko; Yoshida, Hiroyuki; Akazawa, Yumiko; Yamazaki, Kohei; Ota, Yukiko; Sayo, Tetsuya; Takahashi, Yoshito
Abstract: Background: Hyaluronan (HA) has a unique hydration capacity that contributes to firmness and bounciness of the skin. Epidermal HA declines with skin aging, which may lead to clinical signs of aging including skin wrinkles and loss of hydration and elasticity. Recently, we developed a new cosmetic agent 1‐ethyl‐ β ‐ N ‐acetylglucosaminide ( β ‐NAG2), which enhances HA production in cultured human keratinocytes. The aim of this study was to explore antiaging potential of β ‐NAG2 in reconstructed human epidermal models and human clinical trial. Materials and methods: The amount of HA in β ‐NAG2‐treated epidermal models by topical application was analyzed by enzyme‐linked immunosorbent assay (ELISA)‐like assay. A randomized, double‐blind and placebo‐controlled study was conducted in Japanese females ( n  = 33) by topically treating each side of the face with a lotion formulated with β ‐NAG2 or placebo for 8 weeks. Results: Topically applied β ‐NAG2 dose dependently increased HA production in epidermal models. Treatment with β ‐NAG2‐formulated lotion significantly improved skin hydration and elasticity and reduced skin wrinkling in crow's foot areas when compared to the placebo formulation. Conclusion: Topically applied β ‐NAG2 promoted epidermal HA production in vitro and showed antiwrinkle activity in vivo accompanying the improvement in skin hydration and elasticity. Our study provides a novel strategy for antiwrinkle care through β ‐NAG2‐induced epidermal HA production.